Aqueous two-phase systems based on cholinium salts and tetrahydrofuran and their use for lipase purification - Souza, Ranyere L.
Aqueous two-phase systems (ATPS) formed with cholinium-based ionic liquid - ILs (or salts) are a novel, low cost, and high efficient technique for the recovery of biomolecules. This study examines the formation of ATPS based on cholinium-based salts (cholinium chloride, cholinium bitartrate and cholinium dihydrogencitrate) and tetrahydrofuran (THF) for the purification of lipase from Bacillus sp. ITP-001, produced by submerged fermentation. The optimum conditions for this purification were determined to be 40 wt% of THF and 30 wt% of cholinium bitartrate at 25 degrees C. A purification factor of 130.1 +/- 11.7 fold, a lipase yield of 90.0 +/- 0.7% and a partition coefficient of enzyme for IL-rich phase (K-E = 0.11 +/- 0.01) and protein contaminants for THF-rich phase (K-P = 1.16 +/- 0.1) were achieved. (C) 2015 Elsevier B.V. All rights reserved.